2023
DOI: 10.1007/s10389-023-01825-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status with cardiovascular disease and cardiovascular risk factors: a systematic review and meta-analysis

Abstract: Aim Cardiovascular disease (CVD) remains one of the leading causes of mortality worldwide, and several studies have indicated the association between socioeconomic status (SES) with CVD and cardiovascular risk factors (CVRFs). It is necessary to elucidate the association of SES and CVRFs with CVD. Subject and methods We searched PubMed, Embase, Web of Science, and the Cochrane Library for publications, using “socioeconomic status,” “cardiovascular disease,” and correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…The association between lower educational level and high metabolic risk in our study is in accordance with a large amount of evidence that has shown an increased prevalence of cardiovascular risk factors, an increased risk of cardiovascular events and cardiovascular death associated with a lower level of education 19 . An inverse association between years of education and cardiovascular risk factors has been shown 19,20 , principally with HSBP 11,19,20 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The association between lower educational level and high metabolic risk in our study is in accordance with a large amount of evidence that has shown an increased prevalence of cardiovascular risk factors, an increased risk of cardiovascular events and cardiovascular death associated with a lower level of education 19 . An inverse association between years of education and cardiovascular risk factors has been shown 19,20 , principally with HSBP 11,19,20 .…”
Section: Discussionsupporting
confidence: 92%
“…The association between educational level and total family income was expected because as a structural determinant of health, lower educational levels in childhood are associated with lower socioeconomic status in adulthood 11,19,20 . The strong association of lower education/lower income with adult HSBP, high metabolic risk and high multimorbidity could be associated with multiple intermediary risk factors across lifespan, such as unhealthy lifestyle (like physical inactivity in women) and higher exposure to toxins 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings of strong graded associations between lower educational attainment/income with increasing ASCVD risk are consistent with other studies ( Woodward et al, 2015 ). A recent meta-analysis by Wang et al (2023) found that the risk of CVD incidence in low-income groups was 22 % higher than that in high-income groups across 21 included studies. Further, across 10 studies, CVD incidence was 44 % higher in the low education groups when compared to high education groups ( Wang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, use of such medications as preventive measures against CVD events might explain the overestimation of CVD risk seen in our study. In addition, the model does not consider lifestyle behaviours and other factors like socioeconomic status, which can have a considerable impact on cardiovascular health 28 29…”
Section: Discussionmentioning
confidence: 99%